Online product review, product knowledge, attitude, and online purchase behavior - Yap, CS Yap; Ong, M.; Ahmad, R. (2017)
Copyright © 2017, IGI Global. This study examines the influence of online product review and product knowledge on the attitude towards online shopping, which leads to online purchase behavior. Data are collected from an online questionnaire with the use of Google Forms posted on three popular toy enthusiast websites in Malaysia. Using a self-selected sampling procedure, 263 usable responses are obtained. Partial Least Squares Path Modeling (PLS-PM), using R, is performed to test the research hypotheses. Results show that, in general, respondents perceive online product review as a helpful tool in enabling them to learn more about toy products and in making them feel confident in purchasing toys online. Results also reveal that both perceived helpfulness of online product review and consumers' product knowledge are positively related to attitude towards online shopping. Similarly, a positive attitude towards online shopping leads to actual online purchases of toy products. Attitude is found to mediate the relationship between perceived helpfulness of online product review and online purchase behavior. This study suggests that firms should use online product review as an innovative marketing tool to acquire market intelligence and to establish ongoing rapport with their online customers.